2009
DOI: 10.1021/jf902573k
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Dieldrin Uptake in Cucumber and Solvent-Extractable Residue in Soil

Abstract: To prevent the distribution of cucumbers with dieldrin contamination exceeding the limit set by the Japanese Food Sanitation Law, the extraction solvent for dieldrin-contaminated soil was selected prior to cultivation so that the dieldrin residue level in cucumber could be predicted. The exhaustive extraction from soil could not explain the dieldrin uptake by cucumber plants. However, significant correlation (R(2) = 0.966, P < 0.001) was observed between dieldrin concentrations in cucumber and dieldrin concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
5
14
0
Order By: Relevance
“…1) in this study was similar to that reported by Sakai et al, 11) the coe cients of determination (R 2 ) of the regression lines for all cultivars of cucumbers were lower than those in the results obtained by Sakai et al 11) (Fig. 3).…”
Section: Relationship Between Dieldrin Concentrations In Cucumber Frusupporting
confidence: 91%
See 4 more Smart Citations
“…1) in this study was similar to that reported by Sakai et al, 11) the coe cients of determination (R 2 ) of the regression lines for all cultivars of cucumbers were lower than those in the results obtained by Sakai et al 11) (Fig. 3).…”
Section: Relationship Between Dieldrin Concentrations In Cucumber Frusupporting
confidence: 91%
“…In contrast, the latter technique has a time advantage because soil analysis allows prediction of the concentration before cultivation. However, results of Sakai et al 11) were not obtained from cucumber fruits, but from cucumber shoots in the early growth stage grown in a pot.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations